Towards a Study of the Lexicon of Sex and HIV/AIDS (Nordic Journal of African Studies, 2004)
The first HIV/AIDS case in Malawi was diagnosed in 1985. Some medical practitioners, however, date the arrival of HIV/AIDS in Malawi from 1977. The advent of this fatal health condition was then made public to the nation of Malawi through a newspaper article and radio broadcasts on the then only broadcasting outlet, namely, the Malawi Broadcasting Corporation (MBC). The news of the outbreak of HIV/AIDS was received in different ways by different sections of the community. Three types of reactions may be noted for the purpose of this paper. The first reaction was one of shock and fear of this hitherto largely unknown ailment. Other people reacted by simply observing that the disease had always been there as evidenced by such names as magawagawa (they that you share) and kaliwondewonde (it that causes thinness). The third type of reaction was the ‘so what’ kind of response which pointed towards the fact that Malawians should not be unduly worried because it was a known fact that humans are destined to die sooner or later anyway. This paper aims to interrogate the relationship that obtains between cultural pursuits and dictates and the language that is employed in discussing matters of sex and HIV/AIDS. The paper examines the type of language and linguistic expressions, which are used in discussions about sex and sexual behaviour against the backdrop of a generally conservative and male dominated society. The conservative nature of the Malawian society is reflected in a kind of self-censored nature of linguistic use through the employment of euphemistic expressions. In addition, the paper also studies the language that is employed to discuss the HIV/AIDS pandemic. The conclusion reached is that most of the images invoked in such linguistic repertoire are those of being trapped by fatalistic determinism. If we accept that language is a reflection of a people’s culture and the manner in which the people perceive themselves as well as others, the implication of the language use is that certain sections of the community are not part of the national efforts and movements whose aim is to combat and arrest the spread of the fatal virus and all its concomitant socio-economic and cultural consequences. The language use also points out towards the fact that there is partial failure in attempts to effectively communicate about the obvious dangers of the disease whose spread in some cases is oiled by rampant and unacceptable poverty levels as well as lack of genuine empowerment of females to discuss and negotiate for safe sexual practices.